APLIKASI PEMBELAJARAN PENGENALAN ANGKA BERBASIS ANDROID PADA TK AISYAH AMBARAWA BARAT - Taufik M,T.I (Journal of Islamic Education and Learning, 2021)
Learning media in this era do not only use book media, but in various ways. Seeing the rapid development of today's technology that allows adults and even children to hold gadgets or smartphones, of course, it requires contributions in educational applications to develop education in Indonesia. Number recognition applications will be very helpful to increase the value of small children's learning for early understanding of calculations and all kinds of numbers. This is due to the lack of understanding of children about how teachers or parents convey in the learning process, because they still use book media so it is less effective. Based on these problems, the author makes an android-based number recognition application, this research uses the method of observation and literature study. The results of this study are implemented in an Android-based number recognition application, while some of the features contained in the application are number recognition, addition, and subtraction